Implementasi Kuota 30% Keterwakilan Perempuan dalam Pemilu Anggota DPRD Kota Samarinda 2024 - Muhammad Riyan Adi Saputra; Rustiana (International Journal of Politic, Public Policy and Environmental Issues, 2024)
This study aims to analyze the implementation of the 30% women's representation quota in the 2024 legislative elections for the Samarinda City DPRD, based on Law Number 7 of 2017 concerning General Elections. The research method employed is empirical juridical, with data collection through interviews with members of the General Election Commission (KPU) and representatives of political parties, as well as document studies related to the topic. The findings indicate that although the 30% quota has been implemented, various challenges persist, such as the low interest of women in entering politics, societal stereotypes that view politics as a male domain, and the strong patriarchal culture still present in society. Additionally, the lack of family support for women wishing to participate in politics also serves as a hindrance. This research found that while the percentage of women's representation in candidacy reached 36.90%, the number of women elected to the DPRD decreased compared to the previous election. Therefore, this study is expected to provide recommendations for political parties and related institutions to enhance women's representation in politics and promote gender equality in Indonesia through better political education and support.